Microcapsule particle and method for producing the same

JP2024047260A5Pending Publication Date: 2025-03-13AGC INC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022152784
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2025-03-13

AI Technical Summary

Technical Problem

Conventional microcapsule particles face issues with shell layer density and durability due to heat treatment processes that can decompose the functional material, leading to insufficient retention and durability in the medium.

Method used

The method involves adjusting the alkali content in the shell layer and performing heat treatment at a temperature that does not decompose the functional material, using inorganic oxides like silica, and incorporating metals such as Li, Na, K, Rb, Cs, Mg, Ca, and Sr to create a dense shell layer, ensuring reliable retention of the functional material.

Benefits of technology

The resulting microcapsule particles have a dense shell that prevents solvent penetration, maintaining the functional material inside, even in resin compositions, and provide superior durability and stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide microcapsule particles featuring a compact shell and enhanced stability within a medium.SOLUTION: A method for producing microcapsule particles includes forming a shell layer containing inorganic oxide on an outer circumference of a functional material core and then applying heat treatment between 100-800°C, resulting in a microcapsule particle that retains a functional material internally. In the shell layer of the microcapsule particle, the total content of at least one metal M selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba is 10-4,000 mass ppm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to microcapsule particles and a method for producing the same. [Background technology]

[0002] Microcapsule particles are particles that can hold functional materials in the capsules and release them as needed, protecting the functional materials that dissolve in the medium with a shell to prevent them from dissolving into the medium. Such particles are expected to be used in heat storage materials that hold PCM (Phase Change Material).

[0003] In order to meet these requirements, the use of inorganic oxides as the shell has been investigated, and various proposals have been made. For example, Patent Document 1 and Non-Patent Document 1 describe a method for producing microcapsule particles using alkoxysilane. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2020 / 214877 [Non-patent literature]

[0005] [Non-Patent Document 1] Journal of Thermal Analysis and Calorimetry volume 147,pp7077-7097(2022) Summary of the Invention [Problem to be solved by the invention]

[0006] However, conventional microcapsule particles use a shell layer hardening process by heat treatment, which requires hardening at a temperature at which the functional material held therein does not decompose, and as a result, the denseness of the hardened shell layer and its durability in the medium are insufficient.

[0007] The present invention has been made in consideration of the above problems, and has an objective of providing microcapsule particles that have excellent durability in a medium and can reliably retain the internal functional material by adjusting the amount of alkali contained in the shell layer and performing heat treatment at a temperature at which the internal functional material is not decomposed. [Means for solving the problem]

[0008] The present invention relates to the following (1) to (7). (1) A method for producing microcapsule particles, comprising forming a shell layer containing an inorganic oxide on the outer periphery of a functional material core to obtain a microcapsule precursor, and then performing heat treatment at 100 to 800°C to obtain microcapsule particles having a functional material retained therein, wherein the total content of one or more metals M selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba in the shell layer of the microcapsule particles is 10 to 4,000 ppm by mass. (2) The method for producing microcapsule particles according to (1) above, characterized in that the functional material has a weighted average solubility in water of 1 g / 100 mL or less. (3) The method for producing microcapsule particles according to (1) or (2) above, wherein the inorganic oxide contains silica. (4) The method for producing microcapsule particles according to any one of (1) to (3) above, wherein the microcapsule particles have a particle size of 0.1 to 60 μm. (5) The method for producing microcapsule particles according to any one of (1) to (4) above, wherein the microcapsule particles have a median diameter / shell thickness ratio of 0.01 to 0.5. (6) A method for producing microcapsule particles according to any one of (1) to (5) above, characterized in that the microcapsule precursor is subjected to a sealing treatment process in which a silicon source is added to the microcapsule precursor to densify the shell layer, and then a heat treatment is performed. (7) A microcapsule particle comprising a functional material core and a shell layer containing an inorganic oxide surrounding the functional material core, the shell layer containing 10 to 4000 ppm by mass of one or more metals M selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba, and having a retention rate of the functional material in cyclohexane of 35% or more. Effect of the Invention

[0009] According to the present invention, it is possible to provide microcapsule particles having a dense shell layer. Since the microcapsule particles of the present invention are difficult to be permeated by a solvent in a medium, the functional material inside can be reliably maintained even in a resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described below, but the present invention is not limited to the examples in the following description.

[0011] (Microcapsule particles) The microcapsule particles obtained by the present invention are particles with a core-shell structure having a shell layer containing an inorganic oxide and a functional material core inside the shell layer. The presence of a functional material core inside the shell layer can be confirmed by observation with a transmission electron microscope (TEM) or a scanning electron microscope (SEM). In the case of SEM observation, by observing a broken particle with a part open, it can be confirmed that the functional material or a cavity where the functional material has been removed is present inside. In addition, the primary particles of microcapsule particles may partially bond together during the encapsulation and drying processes, and the microcapsule particles obtained by production may be an aggregate of secondary particles formed by aggregation of primary particles.

[0012] Examples of inorganic oxides include silica (SiO2), titanium dioxide, zinc oxide, cerium oxide, copper oxide, iron oxide, tin oxide, etc., and it is preferable to use silica from the viewpoint of ease of shell formation. Hereinafter, the present specification will describe microcapsule particles in which the inorganic oxide contains silica. In this specification, the shell layer "contains silica" means that the shell layer contains 50% or more by mass of silica (SiO2). The composition of the shell layer can be measured by ICP emission spectrometry, flame atomic absorption spectrometry, or the like. The shell layer preferably contains 80% or more by mass of silica, more preferably 95% or more by mass. The upper limit is theoretically 100% by mass. The shell layer preferably contains less than 100% by mass of silica, more preferably 99.99% by mass or less. The remainder includes alkali metal oxides and silicates, alkaline earth metal oxides and silicates, carbon, and the like. In addition, "particles with a core-shell structure" refers to a structure in which a shell layer surrounds a core when a cross section of a single primary particle is observed. In other words, a single microcapsule particle has a single functional material core surrounded by a shell layer. The term "functional material" refers to a water-insoluble substance having a specific function, such as a heat storage material, a fragrance, a medicine, etc. A numerical range expressed using "~" includes the numerical values ​​on either side of the "~" within the numerical range.

[0013] The microcapsule particles of the present invention are particles having a functional material core inside. Applications of the microcapsule particles of the present invention include applications in which the functional material is continuously held inside, applications in which the functional material held inside is gradually released, applications in which the capsules are broken by a stimulus such as friction to release the functional material as needed, and the like. Examples of functional materials that may be retained internally include chromogens and dyes, waxes, skin coolants, sunscreens, reaction catalysts, pigments, UV protection agents, fade inhibitors, phase change materials, and the like. Examples of functional materials used for sustained release include fragrance compositions, fragrance raw materials such as essential oils, vitamins, antioxidants, odor reducers, odor control materials, fabric softeners, insect repellents such as moth repellents, medicines such as medicinal oils, desiccants, chlorine bleach odor suppressants, antiallergic agents, natural active substances, fertilizers, nutrients, herbicides, etc. Examples of functional materials used in applications in which the functional material is released by breaking a capsule include fragrance compositions, fragrance raw materials such as essential oils, lubricating oils, silicone oils, fabric softeners, medicines such as medicinal oils, colorants, adhesives, thickeners, drape and foam regulators, smoothing agents, wrinkle inhibitors, sanitizing agents, disinfectants, bacterial inhibitors, mold inhibitors such as mildew inhibitors, antiviral agents, anti-staining agents, dirt release agents, fabric refreshing agents and agents for maintaining a freshly washed feel, dye fixing agents, color retention agents, color restoration / regeneration agents, anti-fading agents, fabric integration agents, anti-abrasion agents, anti-fuzzing agents, foam inhibitors, defoaming agents, fabric comfort agents, shrinkage resistance agents, stretch resistance agents, stretch recovery agents, skin care agents, dyes, and the like. These may be used alone or in combination of two or more kinds within the range in which the oil phase is formed as a single phase. Among the above uses, it is more preferable to use a functional material that is used while being continuously held inside, and it is particularly preferable to use a phase change material. The microcapsule particles holding the phase change material can be used as a heat storage material, etc.

[0014] The sphericity of the microcapsule particles is preferably 0.75 to 1.0. When the sphericity is low, the microcapsule particles become more susceptible to breakage, and the stability in the medium deteriorates. The sphericity can be expressed as the average value obtained by measuring the maximum diameter (DL) and the minimum diameter (DS) perpendicular to the maximum diameter (DL) for each of 100 random particles in a photographic projection obtained by photographing with a scanning electron microscope (SEM), and calculating the ratio (DS / DL) of the minimum diameter (DS) to the maximum diameter (DL). From the viewpoint of light scattering properties, touch, and the like, the sphericity is more preferably 0.80 or more, even more preferably 0.82 or more, even more preferably 0.83 or more, particularly preferably 0.85 or more, even more preferably 0.87 or more, and most preferably 0.90 or more.

[0015] The particle size of the secondary particles of microcapsule particles (the aggregate size when the primary particles aggregate) can be measured by laser scattering. When measuring the aggregate size using an SEM, the particles break when placed in a vacuum environment during SEM observation, making the boundaries between particles unclear and not reflecting the particle size when dispersed. In addition, when measuring using a Coulter counter, the electric field changes are different between microcapsule particles and solid particles, making it difficult to obtain a value that corresponds to the solid particles.

[0016] The average size of the primary particles (average primary particle diameter) is preferably in the range of 0.1 to 60 μm. When the average primary particle diameter is 0.1 μm or more, the flexibility of the resin is unlikely to decrease when the resin composition contains the microcapsule particles of the present invention. Also, when the average primary particle diameter is 60 μm or less, the resin is easy to handle as a filler. From the viewpoint of production reproducibility, the average primary particle size has a lower limit of preferably 100 nm or more, and most preferably 200 nm or more, and an upper limit of more preferably 30 μm or less, further preferably 20 μm or less, and particularly preferably 15 μm or less.

[0017] The size of the primary particles of microcapsule particles can be determined by directly observing the particle size (diameter) through SEM observation. Specifically, the primary particle size of 100 particles is measured from SEM images, and the distribution of primary particle sizes obtained by tallying these up is estimated as the distribution of the overall primary particle size. Through SEM observation, the primary particle size of particles that are difficult to deflocculate can be directly measured.

[0018] The median diameter of the secondary particles of the microcapsule particles is preferably 0.20 to 60 μm. When the median diameter is 0.20 μm or more, the viscosity is not easily increased and the dispersibility is not easily deteriorated when the resin composition containing the microcapsule particles of the present invention is made, so that the median diameter is preferably 0.20 μm or more, more preferably 0.25 μm or more, and even more preferably 0.30 μm or more. Also, when the median diameter is 60 μm or less, when the resin composition is molded into a film, granulation is not easily caused, so that the median diameter is preferably 60 μm or less, more preferably 50 μm or less, even more preferably 30 μm or less, particularly preferably 20 μm or less, and most preferably 15 μm or less.

[0019] The median diameter / shell thickness ratio of the microcapsule particles is preferably 0.01 to 0.5. If it is 0.01 or more, the shell strength is maintained and it becomes difficult to break, and if it is 0.5 or less, the amount of the functional material retained is not reduced and the functionality is not reduced.

[0020] Here, the shell thickness is determined by measuring the shell thickness of individual particles by transmission electron microscopy (TEM).

[0021] The microcapsule particles have a BET specific surface area of ​​0.1 to 300 m 2 / g. The BET specific surface area is preferably 0.1 m 2 When the microcapsule particles of the present invention are used in a resin composition, the microcapsule particles have a viscosity of 300 m / g or more, and the microcapsule particles have a viscosity of 300 m / g or more. 2 When the molecular weight is 1 / g or less, the functional material can be reliably retained in the solvent. The denser the shell, the smaller the specific surface area. Therefore, the BET specific surface area is 200 m 2 / g or less is more preferable, and 150m 2 / g or less is more preferable, and 50m 2 / g or less is particularly preferable, and 30m 2 The most preferable BET specific surface area is 0.5 m 2 / g or more is more preferable, and 1.0m 2 / g or more is most preferred.

[0022] Here, the BET specific surface area can be measured using a specific surface area measuring device (e.g., Shimadzu Corporation's "Tristar II3020") by drying the microcapsule particles at 120°C to 50 mTorr as a pretreatment, and then using liquid nitrogen in a multi-point method.

[0023] The shell layer of the microcapsule particles contains one or more metals M selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr, and Ba. The inclusion of metal M in the microcapsule particles acts as a flux during firing, reducing the specific surface area and the dielectric tangent. In addition, the shell layer can be made dense even with heat treatment at a lower temperature compared to when metal M is not contained.

[0024] In the production of microcapsule particles, it is preferable that the metal M is contained between the reaction step and the washing step. For example, in the reaction step, the metal salt of the metal M is added to the reaction solution when forming a silica shell, the microcapsule precursor is washed with a solution containing the metal ion of the metal M before sintering, or a silicon source containing the metal ion of the metal M is added to perform a sealing treatment, thereby making it possible to contain the metal M in the microcapsule particles.

[0025] The concentration of metal M contained in the shell layer of the microcapsule particle is 10 to 4000 ppm by mass in total. If the concentration of metal M is 10 ppm by mass or more, sintering proceeds due to the flux effect during firing, and the shell can be made dense. If the concentration is 4000 ppm by mass or less, sintering between particles does not proceed too much, and aggregation is less likely to occur. The concentration of metal M is more preferably 30 ppm by mass or more, more preferably 50 ppm by mass or more. Also, it is preferably 1000 ppm by mass or less, preferably 800 ppm by mass or less, and most preferably 500 ppm by mass or less.

[0026] The metal M can be measured by adding perchloric acid and hydrofluoric acid to the microcapsule particles, igniting them to remove the main component, silicon, and then measuring it using ICP atomic emission spectrometry. Furthermore, when an alkali metal silicate is used as the silica raw material, the shell layer of the obtained microcapsule particles contains less carbon (C) component derived from the raw material, compared to when a silicon alkoxide is used as the silica raw material.

[0027] The surface of the microcapsule particles may be treated with a silane coupling agent. By treating with a silane coupling agent, the affinity with the resin is improved when the microcapsule particles are made into a resin composition, and the dispersibility and strength of the resin film after formation are improved.

[0028] Examples of the silane coupling agent include aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, organosilazane compounds, etc. The silane coupling agents may be used alone or in combination of two or more.

[0029] The amount of the silane coupling agent attached is preferably 1 part by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2 parts by mass or more, per 100 parts by mass of the microcapsule particles, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less.

[0030] The fact that the surface of the microcapsule particles has been treated with a silane coupling agent can be confirmed by detecting a peak due to a substituent of the silane coupling agent by IR. The amount of the silane coupling agent attached can be measured by the amount of carbon.

[0031] (Method of manufacturing microcapsule particles) The method for producing the microcapsule particles of the present invention includes, for example, a method of obtaining a microcapsule precursor in an oil-in-water emulsion containing a water phase, an oil phase containing a functional material, and a surfactant, and obtaining the microcapsule particles from the precursor. This oil-in-water emulsion is an emulsion in which an oil phase is dispersed in water. When a silica raw material is added to this emulsion, the silica raw material adheres to the surface of the oil droplets, and functional material core-silica shell particles can be formed.

[0032] The method for producing microcapsule particles of the present invention includes forming a shell layer containing silica on the outer periphery of a core to obtain a microcapsule precursor, and heat-treating the microcapsule precursor at 100 to 800° C. When obtaining the microcapsule precursor, it is preferable to add a first silica raw material to an oil-in-water emulsion containing an aqueous phase, an oil phase, and a surfactant to form a first shell, and then add a second silica raw material to the emulsion in which the first shell has been formed to form a second shell, thereby obtaining the microcapsule precursor. Hereinafter, the oil-in-water emulsion is also simply referred to as emulsion. In addition, the dispersion liquid in which the functional material core-silica shell particles are dispersed, which is generated by adding the first silica raw material and before the second silica raw material is added, and the dispersion liquid in which the functional material core-silica shell particles are dispersed after the second silica raw material is added, may also be referred to as emulsion. The latter dispersion liquid in which the functional material core-silica shell particles are dispersed after the second silica raw material is added may be the same as the microcapsule precursor dispersion liquid.

[0033] <Formation of the first shell> First, a first silica raw material is added to an oil-in-water emulsion containing an aqueous phase, an oil phase, and a surfactant to form a first shell.

[0034] The aqueous phase of the emulsion mainly contains water as a solvent. The aqueous phase may further contain additives such as water-soluble organic liquids and water-soluble resins. The proportion of water in the aqueous phase is preferably 50 to 100% by mass, more preferably 90 to 100% by mass.

[0035] The oil phase of the emulsion contains a water-insoluble functional material that is incompatible with the aqueous phase components. This functional material forms oil droplets in the emulsion and forms the functional material core portion of the microcapsule precursor.

[0036] As mentioned above, examples of functional materials include colorants and dyes, fragrance compositions, fragrance raw materials such as essential oils, lubricating oils, silicone oils, waxes, lipids, vitamins, sunscreens, antioxidants, reaction catalysts, odor reducers, odor control materials, fabric softeners, insect repellents such as moth repellents, colorants, pigments, medicines such as medicinal oils, adhesives, thickeners, drape and foam regulators, smoothing agents, wrinkle inhibitors, sanitizing agents, disinfectants, bacteria inhibitors, mold inhibitors such as mildew inhibitors. antibacterial, antiviral, drying, stain resistant, soil release, fabric refreshing and fresh feeling agents, chlorine bleach odor control, dye fixatives, color retention, color restoration / regenerators, anti-fade agents, fabric integration agents, anti-abrasion agents, anti-fuzzing agents, foam suppressors, defoamers, UV protection agents, sun fade inhibitors, anti-allergy agents, fabric comfort agents, shrink resistance agents, stretch resistance agents, stretch recovery agents, skin care agents, natural actives, dyes, phase change materials, fertilizers, nutrients, and herbicides.

[0037] These may be used alone or in combination of two or more kinds within the range of forming a single oil phase. Of the above-mentioned functional materials, from the viewpoint of being preferably used in a state in which they are continuously retained inside, it is more preferable to use chromogens and dyes, waxes, skin cooling agents, sunscreens, reaction catalysts, pigments, ultraviolet protection agents, fading inhibitors, phase change materials, etc., and it is even more preferable to use phase change materials. Specific examples of phase change materials include hydrocarbons (e.g., straight chain alkanes or paraffinic hydrocarbons, branched chain alkanes, unsaturated hydrocarbons such as alkynes and alkenes, halogenated hydrocarbons and alicyclic hydrocarbons), fatty acids (e.g., caproic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid and cerotic acid), fatty acid esters (e.g., methyl caprylate, methyl caprate, methyl laurate, methyl myristate, methyl palmitate, methyl stearate, methyl arachidate, methyl behenate, methyl lignocerate), fatty alcohols (e.g., capryl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, lignoceryl alcohol, ceryl alcohol, montanyl alcohol, myricyl alcohol and geddyl alcohol), and the like.alcohol), aromatic compounds, acid anhydrides (e.g., stearic anhydride), sugar alcohols (e.g., erythritol, D-mannitol, galactitol, xylitol, D-sorbitol), polymers (e.g., polyethylene, polyethylene glycol, polyethylene oxide, polypropylene, polypropylene glycol, polytetramethylene glycol, polypropylene malonate, polyneopentyl glycol sebacate, polypentane glutarate, polyvinyl myristate, polyvinyl stearate, polyvinyl laurate, polyhexadecyl methacrylate, polyoctadecyl methacrylate, homopolymers of polyesters produced by polycondensation of glycols (or their derivatives) with diacids (or their derivatives) and copolymers containing them). mers), for example, copolymers of polyacrylate or poly(meth)acrylate with alkyl hydrocarbon side chains or polyethylene glycol side chains (for example, homopolymers of polyethylene, polyethylene glycol, polyethylene oxide, polypropylene, polypropylene glycol, or polytetramethylene glycol, and copolymers containing them), hydrated salts coated with a hydrocarbon or the like to make them insoluble in water (for example, calcium chloride hexahydrate, calcium bromide hexahydrate, magnesium nitrate hexahydrate, lithium nitrate trihydrate, potassium chloride tetrahydrate, ammonium alum, magnesium chloride hexahydrate, sodium carbonate decahydrate, sodium phosphate disodium dodecahydrate, sodium sulfate decahydrate, and sodium acetate trihydrate), metals, and mixtures thereof. Also, a phase change material can be obtained by combining these phase change materials. Among these, organic phase change materials are preferred, with hydrocarbons, fatty acids, and fatty acid esters being more preferred, and hydrocarbons being particularly preferred. As the hydrocarbon, it is preferred to use alkanes, and among these, it is more preferred to use paraffin hydrocarbons. The microcapsule particles holding the phase change material can be used as a heat storage material, etc. When used as a heat storage material, it is preferred that the heat storage capacity of the microcapsule particles when made into a coating film is 10 J / g or more.

[0038] The functional material is selected taking into consideration a comprehensive range of factors, such as ease of use, safety against fire, separability between the microcapsule precursor and the functional material, shape characteristics of the microcapsule particles, and solubility of the functional material in water.

[0039] The flash point of the functional material is preferably 20°C or higher, and more preferably 40°C or higher. When a functional material with a flash point of 20°C or higher is used, the flash point is not too low, and fire prevention and work environment measures are not necessary. In addition, the solubility of the functional material in water is preferably 1g / 100mL or lower on a weighted average. If the solubility is 1g / 100mL or lower, the emulsion can be formed without the functional material dissolving in water when preparing the emulsion.

[0040] The emulsion contains a surfactant to enhance emulsion stability. The surfactant is preferably water-soluble or water-dispersible, and is preferably added to the aqueous phase. A nonionic surfactant is preferred. Examples of the nonionic surfactant include the following surfactants. Polyoxyethylene-polyoxypropylene copolymer surfactants, Polyoxyethylene sorbitan fatty acid ester surfactants: polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, Polyoxyethylene higher alcohol ether surfactants: polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenol ether, polyoxyethylene nonylphenol ether, Polyoxyethylene aliphatic ester surfactants: polyoxyethylene glycol monolaurate, polyoxyethylene glycol monostearate, polyoxyethylene glycol monooleate, Glycerol fatty acid ester surfactants: stearate monoglyceride, oleate monoglyceride. Furthermore, polyoxyethylene sorbitol fatty acid ester surfactants, sucrose fatty acid ester surfactants, polyglycerin fatty acid ester surfactants, polyoxyethylene hydrogenated castor oil surfactants, etc. may also be used. These may be used alone or in combination of two or more.

[0041] Among the above nonionic surfactants, sorbitan fatty acid esters and polyoxyethylene-polyoxypropylene copolymer surfactants can be preferably used. Polyoxyethylene-polyoxypropylene copolymers are block copolymers in which polyoxyethylene blocks (EO) and polyoxypropylene blocks (PO) are bonded. Examples of block copolymers include EO-PO-EO block copolymers and EO-PO block copolymers, and EO-PO-EO block copolymers are preferred. The proportion of oxyethylene units in the EO-PO-EO block copolymer is preferably 20% by mass or more, more preferably 30% by mass or more. The weight average molecular weight of the polyoxyethylene-polyoxypropylene copolymer is preferably from 3,000 to 27,000, and more preferably from 6,000 to 19,000. The total amount of polyoxyethylene blocks is preferably 40 to 90% by mass, and the total amount of polyoxypropylene blocks is preferably 10 to 60% by mass, based on the entire polyoxyethylene-polyoxypropylene copolymer.

[0042] The amount of surfactant used varies depending on conditions such as the type of surfactant, HLB (Hydrophile-lipophile balance), which is an index showing the degree of hydrophilicity or hydrophobicity of the surfactant, and the particle size of the target silica particles, but the content in the aqueous phase is preferably 500 to 20,000 mass ppm, more preferably 1,000 to 10,000 mass ppm. When the content is 500 mass ppm or more, the emulsion can be more stabilized. Also, when the content is 20,000 mass ppm or less, the amount of surfactant remaining in the microcapsule particles can be reduced.

[0043] The water phase and the oil phase may be mixed in a mass ratio of 200:1 to 5:1, and preferably 100:1 to 9:1.

[0044] The method for preparing an oil-in-water emulsion is not limited to the following. The aqueous phase and the oil phase are prepared in advance, and the oil phase is added to the aqueous phase, and the emulsion is thoroughly mixed or stirred to prepare the emulsion. Furthermore, methods such as ultrasonic emulsification, stirring emulsification, and high-pressure emulsification, which apply strong physical shear force, can be applied. In addition, there are methods such as a membrane emulsification method in which an oil phase is made fine through a membrane having fine holes and dispersed in an aqueous phase, a phase inversion emulsification method in which a surfactant is dissolved in an oil phase and then an aqueous phase is added to emulsify, and a phase inversion temperature emulsification method that utilizes the fact that a surfactant changes from water-soluble to oil-soluble at a temperature near the cloud point. These emulsification methods can be appropriately selected depending on the target particle size, particle size distribution, etc.

[0045] In order to reduce the particle size of the resulting microcapsule particles and narrow the particle size distribution, it is preferable that the oil phase is sufficiently dispersed and emulsified in the aqueous phase. For example, the mixture can be emulsified using a high-pressure homogenizer at a pressure of 10 bar or more, preferably 20 bar or more.

[0046] Furthermore, a step of aging the obtained oil-in-water emulsion can be provided. By providing an aging step, fine emulsions grow preferentially, and the primary particle size distribution of the obtained microcapsule particles becomes narrow. The aging time is preferably 0.5 to 240 hours, more preferably 0.5 to 96 hours, and most preferably 0.5 to 48 hours. The aging temperature is preferably 5 to 80°C, more preferably 20 to 70°C, and most preferably 20 to 55°C.

[0047] In the first shell formation step, a first silica raw material is added to the oil-in-water emulsion. Examples of the first silica raw material include an aqueous solution in which water-soluble silica is dissolved, an aqueous dispersion in which solid silica is dispersed, a mixture of these, and one or more selected from the group consisting of alkali metal silicate, active silicic acid, and silicon alkoxide, or an aqueous solution or dispersion thereof. Among these, one or more selected from the group consisting of alkali metal silicate, active silicic acid, and silicon alkoxide, or an aqueous solution or dispersion thereof, is preferred in terms of high availability.

[0048] Examples of solid silica include silica sol obtained by hydrolysis of an organosilicon compound and commercially available silica sol. Examples of the alkali metal of the alkali metal silicate include lithium, sodium, potassium, rubidium, etc., and among them, sodium is preferred due to its availability and economical reasons. That is, sodium silicate is preferred as the alkali metal silicate. Sodium silicate has a composition represented by Na2O·nSiO2·mH2O. The ratio of sodium to silicic acid is preferably 1.0 to 4.0, more preferably 2.0 to 3.5, in terms of the molar ratio n of Na2O / SiO2.

[0049] Activated silicic acid is obtained by replacing alkali metal with hydrogen by cation exchange treatment of alkali metal silicate, and an aqueous solution of this activated silicic acid is weakly acidic. A hydrogen cation exchange resin can be used for the cation exchange. The alkali metal silicate and active silicic acid are preferably dissolved or dispersed in water before being added to the emulsion. The concentration of the alkali metal silicate and active silicic acid aqueous solution is preferably 3 to 30 mass %, more preferably 5 to 25 mass %, in terms of SiO2 concentration.

[0050] As the silicon alkoxide, for example, tetraalkylsilanes such as tetramethoxysilane, tetraethoxysilane, and tetrapropoxysilane can be preferably used. It is also possible to obtain composite particles by mixing other metal oxides, etc. with the silica raw material. Examples of other metal oxides include titanium dioxide, zinc oxide, cerium oxide, copper oxide, iron oxide, and tin oxide.

[0051] As the first silica raw material, the above-mentioned silica raw materials can be used alone or in combination of two or more. Among them, it is preferable to use an aqueous solution of an alkali metal silicate, particularly an aqueous solution of sodium silicate, as the first silica raw material.

[0052] The first silica raw material is preferably added to the oil-in-water emulsion under acidic conditions. By adding the silica raw material under an acidic environment, silica fine particles are generated to form a network, forming the first-stage coating. The reaction temperature is preferably 80°C or less in order to maintain the stability of the emulsion, more preferably 70°C or less, even more preferably 60°C or less, particularly preferably 50°C or less, and most preferably 40°C or less. In addition, from the viewpoint of controlling the network formation rate of the silica fine particles to make the coating thickness uniform, the reaction temperature is preferably 4°C or more, more preferably 10°C or more, even more preferably 15°C or more, particularly preferably 20°C or more, and most preferably 25°C or more.

[0053] From the viewpoint of making the coating thickness more uniform and making the silica shell layer of the obtained microcapsule particles denser, the pH of the oil-in-water emulsion is more preferably less than 3, even more preferably 2.5 or less, and particularly preferably 1 or more.

[0054] The pH of the oil-in-water emulsion can be made acidic by adding an acid. Examples of the acid include hydrochloric acid, nitric acid, sulfuric acid, acetic acid, perchloric acid, hydrobromic acid, trichloroacetic acid, dichloroacetic acid, methanesulfonic acid, and benzenesulfonic acid.

[0055] In the addition of the first silica raw material, the amount of the first silica raw material added is preferably such that the SiO2 content in the first silica raw material is 1 to 50 parts by mass, more preferably 3 to 30 parts by mass, per 100 parts by mass of the oil phase contained in the emulsion.

[0056] In the addition of the first silica raw material, after the addition of the first silica raw material, the emulsion is preferably maintained in an acidic pH state for 1 minute or more, more preferably 5 minutes or more, and even more preferably 10 minutes or more.

[0057] Next, it is preferable to maintain the pH of the emulsion to which the first silica raw material has been added at 3 or more and 7 or less (weakly acidic to neutral), which allows the first silica raw material to be immobilized on the surface of the oil droplets. For example, there is a method of adjusting the pH of the emulsion to 3 or more by adding a base to the emulsion to which the first silica raw material has been added.

[0058] Examples of the base include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkaline earth metal hydroxides such as magnesium hydroxide and calcium hydroxide, ammonia, and amines. Alternatively, a method in which anions such as halogen ions are exchanged for hydroxide ions by anion exchange treatment may be used.

[0059] When adding the base, it is preferable to gradually add the base while stirring the emulsion to which the first silica raw material has been added, so as to gradually increase the pH of the emulsion. If the stirring is weak or a large amount of base is added at once, the pH of the emulsion may become non-uniform, and the thickness of the first coating layer may become non-uniform.

[0060] The emulsion is preferably held while being stirred. The holding time may be 10 minutes or more, preferably 1 hour or more, and may be 4 hours or more. The holding temperature is preferably 100°C or less in order to maintain the stability of the emulsion, more preferably 95°C or less, even more preferably 90°C or less, and particularly preferably 85°C or less. In order to promote aging, the holding temperature is preferably 35°C or more, more preferably 40°C or more, and particularly preferably 45°C or more.

[0061] <Formation of the second shell> Next, a second silica raw material is added to the emulsion in the presence of alkali metal ions, thereby obtaining a microcapsule precursor dispersion, in which the microcapsule precursor is a functional material core-silica shell particle.

[0062] The addition of the second silica source to the emulsion is preferably carried out under alkaline conditions. When the first silica raw material is added, the emulsion is first made acidic, and then the pH is adjusted to between 3 and 7 (weakly acidic to neutral) in order to ensure more uniform adhesion of the first silica raw material to the oil droplet surface. The first silica layer obtained by this method is porous and has insufficient density, resulting in low strength. When the second silica raw material is added, the emulsion is made alkaline, allowing a high-density second silica layer to be formed on the first silica layer obtained earlier.

[0063] The pH of the emulsion when the second silica raw material is added is preferably 8 or more, more preferably 8.5 or more, even more preferably 8.7 or more, particularly preferably 8.9 or more, and most preferably 9 or more, in order to suppress the generation of new fine particles. Also, in order to suppress the solubility of silica from becoming too high, the pH is preferably 13 or less, more preferably 12.5 or less, even more preferably 12 or less, particularly preferably 11.5 or less, and most preferably 11 or less.

[0064] The pH of the oil-in-water emulsion can be made alkaline by adding a base, the same compounds as those mentioned above being used as the base.

[0065] As the second silica raw material, the same as the first silica raw material described above can be used alone or in combination of two or more. Among them, when adding the second silica raw material, at least one of an aqueous solution of sodium silicate and an aqueous solution of active silicic acid can be preferably used. When the second silica raw material is added under alkaline conditions to the emulsion, a method of adding an alkali metal hydroxide simultaneously with the second silica raw material may be used. Alternatively, a method of using sodium silicate as an alkali metal silicate in the second silica raw material may be used. In this case, the sodium silicate component, which is an alkaline component, is added to the weakly acidic emulsion whose pH is set to 5 or more after the addition of the first silica raw material, so that the pH of the emulsion can be kept alkaline while the second silica raw material is added. Also, alkali metal ions become present in the emulsion.

[0066] In addition, when using an aqueous solution of sodium silicate as the second silica raw material, etc., if the pH becomes too high, an acid may be added to adjust the pH. The acid used here may be the same acid used when adding the first silica raw material.

[0067] The second silica raw material is preferably added in the presence of an alkali metal ion. The alkali metal ion may be derived from the first silica raw material, the second silica raw material, or a base added for pH adjustment, and may also be added by adding an additive to the emulsion. For example, an alkali metal silicate is used as at least one of the first silica raw material and the second silica raw material. Also, an alkali metal halide, sulfate, nitrate, fatty acid salt, etc. is used as an additive to the emulsion.

[0068] The second silica raw material may be added, for example, by adding one or both of an aqueous sodium silicate solution and an aqueous active silicic acid solution to the emulsion after the addition of the first silica raw material. When both are added, the aqueous sodium silicate solution and the aqueous active silicic acid solution may be added all at once or in order.

[0069] For example, the addition of the second silica raw material can be performed once or twice or more repeatedly by adding a step of adding an aqueous sodium silicate solution and a step of adding an aqueous active silicic acid solution while adjusting the pH in order to promote adhesion of the silica raw material onto the first silica layer.

[0070] The second silica raw material is preferably added to the heated emulsion in order to promote adhesion of the silica raw material onto the first silica layer. The heating temperature is preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, particularly preferably 45°C or higher, and most preferably 50°C or higher, in order to suppress the generation of new fine particles. In addition, in order to suppress the solubility of silica from becoming too high, the heating temperature is preferably 100°C or lower, more preferably 95°C or lower, even more preferably 90°C or lower, particularly preferably 85°C or lower, and most preferably 80°C or lower. When a heated emulsion is used, it is preferable to gradually cool the resulting emulsion to room temperature (about 23°C) after the addition of the second silica raw material.

[0071] In the addition of the second silica raw material, the amount of the second silica raw material added is preferably adjusted so that the amount of SiO2 in the second silica raw material is 20 to 500 parts by mass, and more preferably 40 to 300 parts by mass, per 100 parts by mass of the oil phase. In the addition of the second silica raw material, it is preferable to maintain the emulsion in an alkaline state for 10 minutes or more after the addition of the second silica raw material.

[0072] Through the addition of the first silica raw material and the second silica raw material, the total amount of the first silica raw material and the second silica raw material is preferably adjusted so that the sum of SiO2 in the first silica raw material and SiO2 in the second silica raw material is 30 to 500 parts by mass, and more preferably 50 to 300 parts by mass, per 100 parts by mass of the oil phase.

[0073] The silica shell layer of the present invention is mainly composed of silica, but may contain other metal components such as Ti and Zr as necessary for refractive index adjustment, etc. The method for containing other metal components is not particularly limited, but for example, a method of simultaneously adding a metal sol liquid or a metal salt aqueous solution in the process of adding the silica raw material is used.

[0074] In the manner described above, a microcapsule precursor dispersion is obtained.

[0075] Methods for obtaining the microcapsule precursor from the microcapsule precursor dispersion include, for example, filtering the dispersion, heating to remove the aqueous phase, and isolating the precursor by sedimentation or centrifugation. One example is a method in which the dispersion liquid is filtered using a filter of about 0.1 to 5 μm, and the microcapsule precursor separated by filtration is dried.

[0076] If necessary, the obtained microcapsule precursor may be washed with water, an acid, an alkali, an organic solvent, or the like.

[0077] If necessary, the obtained microcapsule precursor may be subjected to a sealing treatment. The sealing treatment is a treatment in which a silicon source is added to densify the shell. Specifically, various alkoxysilanes, sodium silicate, silica sol, active silicic acid, etc. can be used as the silicon source. In addition, an acid or base may be added as a pH adjuster to keep the pH constant in order to control the reaction. The amount of the silicon source added is preferably 1 part by mass or more, and preferably 500 parts by mass or less, per 100 parts by mass of the microcapsule particles.

[0078] The method for producing microcapsule particles of the present invention also includes a step of incorporating one or more metals M selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr, and Ba into the shell layer. By incorporating metal M into the microcapsule particles, it acts as a flux during firing, reducing the specific surface area and the dielectric tangent. In addition, it is possible to densify the shell layer even with a heat treatment at a lower temperature compared to when metal M is not incorporated.

[0079] In the production of microcapsule particles, it is preferable to incorporate the metal M between the reaction step and the washing step. For example, in the reaction step, the metal salt of the metal M can be added to the reaction solution when forming a silica shell, the microcapsule precursor can be washed with a solution containing the metal ion of the metal M before sintering, or a silicon source containing the metal ion of the metal M can be added to perform a sealing treatment, thereby incorporating the metal M into the microcapsule particles.

[0080] The total content of metal M contained in the microcapsule particles, i.e., the concentration, is 10 to 4000 ppm by mass. If the concentration of metal M is 10 ppm by mass or more, sintering proceeds due to the flux effect during firing, and the shell can be made dense. If the concentration is 4000 ppm by mass or less, sintering between particles does not proceed too much, and aggregation is less likely to occur. The concentration of metal M is more preferably 30 ppm by mass or more, more preferably 50 ppm by mass or more. Also, it is preferably 1000 ppm by mass or less, more preferably 800 ppm by mass or less, and most preferably 500 ppm by mass or less.

[0081] <Heat treatment of microcapsule precursor> The microcapsule precursor is then heat treated to densify it.

[0082] In the method of densifying the microcapsule precursor by heat treatment, the heat treatment temperature is 100 to 800° C. The lower limit of the heat treatment temperature is more preferably 150° C. or higher, and most preferably 200° C. or higher. In order to prevent the functional material contained in the oil phase from being removed or decomposed, the upper limit of the heat treatment temperature is preferably less than 800° C., preferably 500° C. or lower, more preferably 350° C. or lower, and most preferably 300° C. or lower. If necessary, the heat treatment temperature may be in two stages.

[0083] <Surface treatment of microcapsule particles> The microcapsule particles obtained in the above step may then be surface-treated with a silane coupling agent, which makes the surfaces of the microcapsule particles hydrophobic and improves their affinity for resins, thereby improving their dispersibility in resins.

[0084] The conditions for the surface treatment are not particularly limited, and general surface treatment conditions may be used, and a wet treatment method or a dry treatment method may be used. From the viewpoint of performing uniform treatment, the wet treatment method is preferred.

[0085] Examples of the silane coupling agent used in the surface treatment include aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, organosilazane compounds, etc. These may be used alone or in combination of two or more.

[0086] Specific examples of the surface treatment agent include aminosilane coupling agents such as aminopropyl methoxysilane, aminopropyl triethoxysilane, ureidopropyl triethoxysilane, N-phenyl aminopropyl trimethoxysilane, and N-2 (aminoethyl) aminopropyl trimethoxysilane; epoxysilane coupling agents such as glycidoxypropyl trimethoxysilane, glycidoxypropyl triethoxysilane, glycidoxypropyl methyl diethoxysilane, glycidyl butyl trimethoxysilane, and (3,4-epoxycyclohexyl) ethyl trimethoxysilane; mercaptosilane coupling agents such as mercaptopropyl trimethoxysilane and mercaptopropyl triethoxysilane; Silane coupling agents such as methyltrimethoxysilane, vinyltrimethoxysilane, octadecyltrimethoxysilane, phenyltrimethoxysilane, metachloroxypropyltrimethoxysilane, imidazole silane, and triazine silane; CF3(CF2)7CH2CH2Si(OCH3)3, CF3(CF2)7CH2CH2SiCl3, CF3(CF2)7CH2CH2Si(CH3)(OCH3)2, CF3(CF2)7CH2CH2Si(CH3)C12, CF3(CF2)5CH2CH2SiCl3, CF3(CF2)5CH2CH2Si(OCH3)3, CF3CH2CH2SiCl3, CF3CH2CH2Si(OCH3)3, C8F 17 SO2N(C3H7)CH2CH2CH2Si(OCH3)3, C7F 15 CONHCH2CH2CH2Si(OCH3)3, C8F 17 CO2CH2CH2CH2Si(OCH3)3, C8F 17 Fluorine-containing silane coupling agents such as -O-CF(CF3)CF2-O-C3H6SiCl3 and C3F7-O-(CF(CF3)CF2-O)2-CF(CF3)CONH-(CH2)3Si(OCH3)3; and organosilazane compounds such as hexamethyldisilazane, hexaphenyldisilazane, trisilazane, cyclotrisilazane, and 1,1,3,3,5,5-hexamethylcyclotrisilazane.

[0087] The amount of the silane coupling agent to be used is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less, based on 100 parts by mass of the microcapsule particles.

[0088] Examples of the method for treating with a silane coupling agent include a dry method in which the silane coupling agent is sprayed onto the microcapsule particles, and a wet method in which the microcapsule particles are dispersed in a solvent and then a silane coupling agent is added to cause a reaction.

[0089] The microcapsule particles obtained by the above steps may be aggregated due to the drying or baking steps, so they may be crushed to an aggregate size that is easy to handle. Examples of the crushing method include a method using a mortar, a method using a dry or wet ball mill, a method using a shaking sieve, and a method using a crusher such as a pin mill, a cutter mill, a hammer mill, a knife mill, a roller mill, or a jet mill.

[0090] The microcapsule particles of the present invention have a shell layer that is densified by adjusting the amount of metal M, and therefore have low permeability to various solvents when added to organic solvents such as methyl ethyl ketone and N-methylpyrrolidone. Therefore, the microcapsule particles have good dispersibility in various solvents, and the functional material in the oil phase is less likely to dissolve in the solvent. The microcapsule particles of the present invention have a functional material retention rate in cyclohexane of 35% or more. If the functional material retention rate in cyclohexane is high, the functional material inside can be reliably retained, so that the retention rate is more preferably 50% or more, even more preferably 70% or more, and particularly preferably 85% or more.

[0091] An example of a method for measuring the retention rate in cyclohexane is to add microcapsule particles to cyclohexane and retain them, then measure the mass A of a membrane filter with a mesh size of 0.5 μm in advance, use the filter to perform suction solid-liquid separation, vacuum-dry the resulting filter paper at 120°C for 2 hours, measure the mass B of the membrane filter retaining the obtained microcapsule particles, and then determine the retention rate in cyclohexane as (AB) / 1.

[0092] Furthermore, the microcapsule particles of the present invention have a shell made of an inorganic oxide, and therefore have superior weather resistance compared to those using a resin shell, and can also comply with recent microplastic regulations.

[0093] In addition, since the microcapsule particles of the present invention contain an appropriate amount of metal M, the shell becomes denser when heat-treated at a low temperature compared to microcapsule particles made of alkoxysilane, etc. Therefore, it becomes possible to reliably retain the functional material inside. EXAMPLES

[0094] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the following description, the same components are used. In addition, unless otherwise specified, "%" and "parts" represent "% by mass" and "parts by mass", respectively. Moreover, Examples 1 to 9 are working examples, and Examples 10 and 11 are comparative examples.

[0095] <Test Example 1> (Example 1) "Preparation of emulsion" 4 g of EO-PO-EO block copolymer (ADEKA Pluronic F68) was added to 1250 g of pure water at 40°C and stirred until dissolved. 42 g of Rubitherm RT31 in which 4 g of sorbitan acid monooleate (Sanyo Chemical Industries Ionet S-80) had been dissolved was added to this aqueous solution, and the whole solution was stirred using an IKA homogenizer until it became uniform, producing a crude emulsion. This crude emulsion was emulsified at a pressure of 50 bar using a high-pressure emulsifier (LAB1000 manufactured by SMT Corporation) to produce a fine emulsion with an emulsion diameter of 3 μm.

[0096] "First stage shell formation" To 1300 g of the resulting fine emulsion, 23 g of diluted sodium silicate aqueous solution (SiO2 concentration 10.4%, Na2O concentration 3.6%) and 2M hydrochloric acid were added so as to adjust the pH to 2, and the mixture was thoroughly stirred while maintaining the temperature at 30°C. While thoroughly stirring this liquid, a 1M aqueous solution of sodium hydroxide was slowly added dropwise to obtain a functional material core-silica shell particle dispersion liquid so that the pH became 6. The obtained functional material core-silica shell particle dispersion liquid was retained and aged.

[0097] "Second stage shell formation" The entire amount of the functional material core-silica shell particle dispersion obtained in the first shell formation was heated to 70° C., and 1M NaOH was slowly added with stirring to adjust the pH to 9. Next, 330 g of a diluted aqueous solution of sodium silicate (SiO2 concentration 10.4%, Na2O concentration 3.6%) was gradually added together with 0.5 M hydrochloric acid to adjust the pH to 9. This suspension was kept at 80° C. for 1 day and then cooled to room temperature to obtain a microcapsule precursor dispersion.

[0098] Filtration and cleaning The entire microcapsule precursor dispersion was neutralized to pH 2 with 2M hydrochloric acid, and then filtered using quantitative filter paper 5C to obtain a microcapsule cake.

[0099] "Sealing treatment" The entire amount of the obtained microcapsule cake was added to 1 L of ion-exchanged water and dispersed by stirring. 330 g of active silicic acid (10% silica concentration) with pH=2.5, which was prepared by ion-exchanging No. 3 silicic acid with ion-exchange resin DIAION (manufactured by Mitsubishi Chemical Corporation), and 28% aqueous ammonia solution were added dropwise to the mixture while maintaining the pH at 9. The resulting microcapsule cake was filtered using quantitative filter paper 5C. After that, 1 L of 80°C ion-exchanged water was added and pressure-filtered again to wash the microcapsule cake.

[0100] "Baking" The filtered cake was dried in a nitrogen atmosphere at 100° C. for 1 hour and then at 200° C. for 2 hours (heating rate: 10° C. / min) to obtain microcapsule particles.

[0101] "Surface treatment" 10 g of the microcapsule particles, 150 ml of isopropanol, and 0.1 g of 3-(methacryloyloxy)propyltrimethoxysilane were added to a 200 ml glass beaker and refluxed at 100° C. for 1 hour. The mixture was then filtered under reduced pressure using a hydrophobic PTFE membrane filter, washed with 20 ml of isopropanol, and vacuum-dried for 2 hours in a vacuum dryer adjusted to 150° C. to obtain surface-treated microcapsule particles.

[0102] "evaluation"

[0103] 1. Median diameter The obtained microcapsule particles were measured using a diffraction / scattering type particle distribution analyzer (MT3300) manufactured by Microtrack Bell, and the median value of the particle distribution (diameter) was measured twice to obtain the average value. The median diameter was 3 μm.

[0104] 2.Shell thickness The shell thickness was measured by observation using a transmission electron microscope (TEM), and the shell thickness / median diameter ratio was calculated using the measured shell thickness.

[0105] 3. Concentration of metal M (M = Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba) The microcapsule particles were added with perchloric acid and hydrofluoric acid, and then ignited to remove the main component silicon. The particles were then measured by ICP-AES (inductively coupled plasma atomic emission spectrometry) using an ICPE-9000 (manufactured by Shimadzu Corporation). The measurements detected Na, K, Mg, and Ca as metal M. The total amount of metal M is shown in Table 1.

[0106] 4. Retention in cyclohexane 1 g of the obtained microcapsule particles was added to 10 g of cyclohexane, and then the mixture was kept at 60°C for 24 hours. Then, the mass A of a membrane filter with a mesh size of 0.5 μm was measured in advance, and the filter was used for suction solid-liquid separation. The obtained filter paper was then vacuum-dried at 120°C for 2 hours, and the mass B of the membrane filter holding the obtained microcapsule particles was measured. Then, (AB) / 1(%) was taken as the retention rate in cyclohexane.

[0107] (Example 2) The same procedure as in Example 1 was carried out except that the active silicic acid used in the sealing treatment was 330 g of a diluted aqueous solution of sodium silicate (SiO2 concentration 10.4%, Na2O concentration 3.6%) and 0.25 M sulfuric acid was added dropwise while maintaining the pH at 9.

[0108] (Example 3) The same conditions as in Example 1 were used except that no sealing treatment was carried out.

[0109] (Example 4) The same conditions as in Example 1 were repeated, except that the amount of diluted sodium silicate aqueous solution (SiO2 concentration 10.4%, Na2O concentration 3.6%) used for forming the second shell was changed to 6600 g.

[0110] (Example 5) The same conditions as in Example 1 were repeated, except that the amount of diluted sodium silicate aqueous solution (SiO2 concentration 10.4%, Na2O concentration 3.6%) used in forming the second shell was changed to 110 g.

[0111] (Example 6) The same conditions as in Example 1 were used, except that the amount of EO-PO-EO block copolymer (ADEKA Pluronic F68) was 15 g, sorbitan acid monooleate (Sanyo Chemical Industries, Ltd. Ionet S-80) was not used, and emulsification was performed at a pressure of 100 bar.

[0112] (Example 7) The same procedure as in Example 1 was carried out, except that the crude emulsion was used as is without being subjected to high-pressure emulsification.

[0113] (Example 8) The same procedure as in Example 1 was repeated, except that 350 ml of tap water was added instead of the ion-exchanged water and pressure filtered again.

[0114] (Example 9) The same procedures as in Example 1 were carried out except that 500 ml of 0.1 mol / L acetic acid (Kanto Chemical Co., Ltd.) was added instead of ion-exchanged water and pressure filtration was performed again.

[0115] (Example 10) The same procedure as in Example 1 was repeated, except that 3500 ml of tap water was added instead of the ion-exchanged water and pressure filtered again.

[0116] (Example 11) The same procedures as in Example 1 were carried out except that 500 ml of 1 mol / L sulfuric acid (2N) (Kanto Chemical Co., Ltd.) was added instead of ion-exchanged water and pressure filtration was performed again.

[0117] The above results are summarized in Table 1.

[0118] [Table 1]

[0119] As shown in Table 1, in Examples 1 to 9 in which the metal M in the shell layer was 10 to 4000 mass ppm, the retention rate of the functional material in cyclohexane was 85% or more, indicating that the functional material could be reliably retained inside. In contrast, in Example 10, the metal M was too much, so sintering between the particles progressed and the particles could no longer be handled as particles. In Example 11, the metal M was too little, so the shell layer was not dense, and the retention rate in cyclohexane was significantly reduced to 30%.

[0120] Next, the obtained microcapsule particles were used to form coating films, and the heat storage performance was compared. Specifically, 200 parts of acrylic resin (0403KA, solid content 40%, Taisei Fine Chemical Co., Ltd.) was mixed with 100 parts of the microcapsule particles prepared in Examples 1 and 11, and 50 parts of methyl ethyl ketone, and mixed for 3 minutes at 2000 rpm in a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARE-310) to obtain an acrylic varnish. Next, a release-treated transparent polyethylene terephthalate (PET) film (Lintec Corporation "PET5011 550", thickness 50 μm) was prepared. The release-treated surface of this PET film was coated with the obtained acrylic varnish using an applicator so that the thickness after drying was 100 μm, and dried in a gear oven at 100 ° C for 2 hours. Then, the obtained coating film was released from the PET film, crushed, and placed in a pan for DSC, and the heat storage capacity at 30 to 40 ° C was calculated using a DSC (differential scanning calorimeter). The obtained results are shown in Table 2.

[0121] [Table 2]

[0122] As shown in Table 2, it was found that the coating film produced using the microcapsule particles of Example 1, which had a good retention rate in cyclohexane, had excellent heat storage capacity. On the other hand, when the microcapsule particles of Example 11, which had a low retention rate in cyclohexane, were used, the heat storage capacity was poor. This is thought to be because the durability in the solvent was insufficient, so the functional material inside was lost during the drying process after the coating film was produced, and became compatible with the resin, changing the melting point.

Claims

1. A method for producing microcapsule particles, comprising forming a shell layer containing an inorganic oxide on the outer periphery of a functional material core to obtain a microcapsule precursor, and then performing heat treatment at 100 to 800°C to obtain microcapsule particles having a functional material held therein, wherein the total content of one or more metals M selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba in the shell layer of the microcapsule particles is 10 to 4,000 ppm by mass.

2. The method for producing microcapsule particles according to claim 1 , wherein the functional material has a weighted average solubility in water of 1 g / 100 mL or less.

3. The method for producing microcapsule particles according to claim 1 or 2, wherein the inorganic oxide contains silica.

4. 3. The method for producing microcapsule particles according to claim 1, wherein the microcapsule particles have a particle size of 0.1 to 60 μm.

5. The method for producing microcapsule particles according to claim 1 or 2, wherein the median diameter / shell thickness ratio of the microcapsule particles is 0.01 to 0.

5.

6. The method for producing microcapsule particles according to claim 1 or 2, characterized in that the microcapsule precursor is subjected to a sealing treatment process in which a silicon source is added to densify the shell layer, and then a heat treatment is performed.

7. The microcapsule particles are composed of a functional material core and a shell layer containing an inorganic oxide surrounding the functional material core, the shell layer containing 10 to 4000 ppm by mass in total of one or more metals M selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba, and the retention rate of the functional material in cyclohexane is 35% or more.